C-, O- and Sr-isotope stratigraphy across the Lower-Middle Cambrian transition of the Cantabrian Zone (Spain) and the Montagne Noire (France), West Gondwana - Wotte, T; Alvaro, J; Shields, G; Brown, B; Brasier, M; Veizer, J (2007)
C-, O- and Sr-isotopes have been analysed for three sections of the Cantabrian Zone (northern Spain) and the southern Montagne Noire (France) that cross the Lower-Middle Cambrian transition, or Bilbilian-Leonian transition in its Iberian sense. The base of the Leonian (Middle Cambrian) is regionally defined by the first appearance of the trilobite Acadoparadoxides mureroensis, which is well constrained in the Cantabrian Zone but absent in the Montagne Noire. In the Bilbilian parts of the three sections, nearshore to peritidal strata are capped by erosive unconformities. The succeeding Leonian relative sea-level rise is recorded in similar fashion in both environments, leading to the deposition of aggradational bioclastic limestones and/or transgressive limestone/shale couplets (the so-called griotte facies) overlain by offshore shales, which relate to platform drowning and coastal smothering during the Leonian-Caesaraugustan transition. Bilbilian-Leonian carbonates show a long-term trend to higher δ13C values that was punctuated by a succession of positive excursions. In Crémenes-Valdoré (Cantabrian Zone) and Ferrals-les-Montagnes (Montagne Noire), two Bilbilian δ13C shifts (an older uncertain peak at + 0.1‰/+ 0.01‰ and a younger certain shift at + 0.6‰/+ 1.7‰), and two Leonian shifts (peaking at + 1.1‰/+ 1.2‰ and + 1.3‰, respectively) are apparent; at Genestosa (Cantabrian Zone) a fifth early-middle Caesaraugustan shift is identified (peaking at + 2.1‰). These positive excursions and increasing trend are similar to published trends from the Lower-Middle Cambrian transition in Siberia and Australia, although in those areas only two δ13C excursions have been reported so far. The marked negative δ13C excursion reported from the Lower-Middle Cambrian boundary of Laurentia and China is not recorded in our dataset. Oxygen isotope and trace element (Ca, Mn and Sr) data indicate that our δ13C trends are unlikely to be diagenetic features, while the lack of correlation with relative sea-level fluctuations, facies changes, or benthic community dynamics means that they could be of potential for global stratigraphic correlation. Sr isotope compositions for the Cantabrian Zone succession exhibit consistent values upsection, which suggests that seawater 87Sr/86Sr remained around 0.7089-0.7090. Our more limited dataset for the Montagne Noire region confirms this value, and both are consistent with published constraints from Laurentia for seawater 87Sr/86Sr across the Lower-Middle Cambrian boundary. The only other 87Sr/86Sr study to cover the boundary interval reported significantly lower 87Sr/86Sr values ∼0.7087-0.7088, indicating perhaps that the Lower-Middle Cambrian boundary in Siberia lies stratigraphically below its equivalent levels in Europe and Laurentia. However, we consider it more likely that these Siberian samples have been diagenetically altered to less radiogenic values. © 2007 Elsevier B.V. All rights reserved.